Timed Automata May Cause Some Troubles - Bouyer, Patricia (BRICS Report Series, 2002)
Timed automata are a widely studied model. Its decidability has been proved using the so-called region automaton construction. This construction provides a correct abstraction for the behaviours of timed automata, but it does not support a natural implementation and, in practice, algorithms based on the notion of zones are implemented using adapted data structures like DBMs. When we focus on forward analysis algorithms, the exact computation of all the successors of the initial configurations does not always terminate. Thus, some abstractions are often used to ensure termination, among which, a widening operator on zones. In this paper, we study in details this widening operator and the forward analysis algorithm that uses it. This algorithm is most used and implemented in tools like Kronos and Uppaal. One of our main results is that it is hopeless to find a forward analysis algorithm, that uses such a widening operator, and which is correct. This goes really against what one could think. We then study in details this algorithm in the more general framework of updatable timed automata, a model which has been introduced as a natural syntactic extension of classical timed automata. We describe subclasses of this model for which a correct widening operator can be found.